2014
DOI: 10.1016/j.compbiomed.2014.07.019
|View full text |Cite
|
Sign up to set email alerts
|

A survey of prostate modeling for image analysis

Abstract: Computer technology is widely used for multimodal image analysis of the prostate gland. Several techniques have been developed, most of which incorporate a priori knowledge extracted from organ features. Knowledge extraction and modeling are multi-step tasks. Here, we review these steps and classify the modeling according to the data analysis methods employed and the features used. We conclude with a survey of some clinical applications where these techniques are employed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 135 publications
0
4
0
Order By: Relevance
“…In this section, only the segmentation methods used in CAD for CaP systems are presented and summarized in Table 4, and are mostly intensity based. An exhaustive review of prostate segmentation methods in MRI can be found in [133] as well as prostate modelling in [134].…”
Section: Segmentationmentioning
confidence: 99%
“…In this section, only the segmentation methods used in CAD for CaP systems are presented and summarized in Table 4, and are mostly intensity based. An exhaustive review of prostate segmentation methods in MRI can be found in [133] as well as prostate modelling in [134].…”
Section: Segmentationmentioning
confidence: 99%
“…Manual detection and segmentation of both prostate gland and prostate carcinoma on multispectral MRI is a time-consuming task, which has to be performed by experienced radiologists [245]. In fact, in addition to conventional structural T1w and T2w MRI protocols, complementary and powerful functional information about the tumor can be extracted [104,213,355] from: DCE [174], DWI [240], and MRSI [197,393]. A standardized interpretation of multiparametric MRI is very difficult and significant inter-observer variability has been reported in the literature [507].…”
Section: Prostate Mri Analysismentioning
confidence: 99%
“…Manual detection and segmentation of both prostate gland and prostate carcinoma on multispectral MRI is a time-consuming task, which has to be performed by experienced radiologists [9]. In fact, in addition to conventional structural T1-weighted (T1w) and T2-weighted (T2w) MRI protocols, complementary and powerful functional information about the tumor can be extracted [10][11][12] from: Dynamic Contrast Enhanced (DCE) [13], Diffusion Weighted Imaging (DWI) [14], and Magnetic Resonance Spectroscopic Imaging (MRSI) [15,16]. A standardized interpretation of multiparametric MRI is very difficult and significant inter-observer variability has been reported in the literature [17].…”
Section: Introductionmentioning
confidence: 99%